2020
DOI: 10.3389/fpls.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Analysis and Multi-Locus Genome-Wide Association Studies Identify QTNs Controlling Soybean Plant Height

Abstract: Plant height is an important target for soybean breeding. It is a typical quantitative trait controlled by multiple genes and is susceptible to environmental influences. Here, we carried out phenotypic analysis of 156 recombinant inbred lines derived from "Dongnong L13" and "Henong 60" in nine environments at four locations over 6 years using interval mapping and inclusive composite interval mapping methods. We performed quantitative trait locus (QTL) analysis by applying pre-built simple-sequence repeat maps.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 70 publications
(77 reference statements)
9
7
0
Order By: Relevance
“…A comparison of the four multi-locus methods used indicated that the ISIS-EM-BLASSO method identi ed the highest number of co-detected QTNs, corroborating the ndings of previous studies (Cui et al 2018;Ma et al 2018;Misra et al 2018;Zhang et al 2018b;Fang et al 2020). Although using the pLARmEB method initially detected the greatest number of QTNs, few of these contributed signi cantly to heritability, as previously reported by Li et al (2018) and Lü et al (2018).…”
Section: Discussionsupporting
confidence: 87%
“…A comparison of the four multi-locus methods used indicated that the ISIS-EM-BLASSO method identi ed the highest number of co-detected QTNs, corroborating the ndings of previous studies (Cui et al 2018;Ma et al 2018;Misra et al 2018;Zhang et al 2018b;Fang et al 2020). Although using the pLARmEB method initially detected the greatest number of QTNs, few of these contributed signi cantly to heritability, as previously reported by Li et al (2018) and Lü et al (2018).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, the FASTmrMLM method, while it detected the lowest number of QTNs detected, was considered the most efficient of the methods evaluated. Several studies comparing the ISIS-EM-BLASSO, pLARmEB, mrMLM, and FASTmrMLM methods have already been performed in many crops and the results are similar to those observed in the present study (Ma et al, 2018;Misra et al, 2018;Zhang et al, 2018;Fang et al, 2020). Although the ML-GWAS methods have similar approaches, the differential identification of QTNs is related to different screening and estimation models of each method (Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…Significant increases in productivity (YLD) and its primary components (NPP, SP, TSW, W100) were observed, and alleles that caused a significant PH reduction were identified. The PH is an essential factor in the formation of production components, and at the same time, it promotes or inhibits other components, affecting mainly the resistance to lodging, NN and NPP (Fang et al, 2020). Small-sized plants are associated with a determinate growth habit, less susceptibility to lodging, and shorter cycles (Chang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, research studies have already combined the two methods to conduct target trait location analysis. In soybean, the combination of the two methods was used in several traits, such as seed size and shape (Hu et al, 2013 ), seed protein and oil content (Zhang et al, 2019 ), number of pods (Song et al, 2020 ), and plant height (Fang et al, 2020 ). Similar to the MAGIC population, four parents carried multiple allelic genotypes in FW-RIL, so it could conduct linkage and association analysis (Zhang et al, 2018 ; Li et al, 2019 , 2020 , 2021 ; Liu et al, 2019 ; Qi et al, 2020 ; Song et al, 2020 ; Tian et al, 2020 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%